PENGARUH VOLATILITAS ARUS KAS, VOLATILITAS PENJUALAN, BOOK TAX DIFFERENCE, TINGKAT HUTANG, KOMITE AUDIT DAN KEPEMILIKAN INSTITUSIONAL TERHADAP PERSISTENSI LABA (Studi Pada Perusahaan Manufaktur Tahun 2012-2014) - Dian Wahyu Utami, 12.05.52.0066; Puspitasari, Elen (Students' Journal of Accounting and Banking, 2016)
This research aims to analyze the effect of cash volatility, sale volatility, book tax difference, leverage, audit committe and institutional ownership on earning persistence. Earnings persistence is defined as the profit that can be used as an indicator of future earnings, in other words, the persistence of the earnings of a company's ability to survive in the future. The dependent variabel used in this study is earning persistence in observations 2012-2014. The population of this research is 155 companies in the manufacturing sector which were listed in Indonesian Stock Exchange (IDX). The research data were collected from manufacturing companies financial statement for the period of years 2012-2014. Based on purposive sampling method, there are 31 samples. The reseacrh hypotesis were tested using multiple linear regression analysis. The results indicate that audit committee firm has positive and significant effect on earnings persistence. For cash volatilityfirm has positive and no significant effect on earning persistence. While sales volatility, leverage, institutional ownershipfirm has negative and no significant effect on earnings persistence. But the book tax difference firm has negative and significant effect on earnings persistence.Keywords: Earning Persistence, Cash Volatility, Sales Volatility, Book Tax Difference, Leverage, Audit Committe, Institutional Ownership